Peran Supervisi dan Monitoring Terhadap Kinerja Guru - Siti Alifah (Jurnal Ilmiah Wahana Pendidikan, 2020)
Supervision of the teaching and learning process was a series of final activities in assessing an activity. Class supervision carried out by the principal is an activity that determines the success of a teaching class supervision activity carried out by the principal. The purpose of this study was to determine the effect of classroom supervision and monitoring on teacher performance, the effect of supervision on teacher performance and monitoring of teacher performance. This research method using survey method. The data were collected using a questionnaire. The population in this study were all teachers, totaling 21 junior and senior high school principals in the Bekasi city environment. The data were processed using SPSS 21. The data were processed using normality and homogeneity tests. After that the data were analyzed using multiple regressions. The results showed that supervision had an effect on performance, monitoring had an effect on performance and the effect of simultaneous supervision and monitoring on performance.